Brilliant moon : the autobiography of Dilgo Khyentse - Khyentse, Dilgo (Boston : Shambhala, 2012)
Through lively anecdotes and stories this highly revered Buddhist meditation master and scholar tells about his life of study, retreat, and teaching. The formative events of Dilgo Khyentse Rinpoche$1 (Bs life, and those insights and experiences that caused him to mature into the warm, brilliant, and highly realized meditation master and teacher he was, are deeply inspiring. The second half of the book comprises recollections by his wife; his grandson, Shechen Rabjam Rinpoche; Tenga Rinpoche; the Queen Mother of Bhutan; and many prominent teachers.s
included bibliographical, references and glossary
Keywords: Rab-gsal-zla-ba (Dil-mgo mKhyen-brtse).